Introduction to reference and information services in today's school library - Farmer, Lesley S. J. (Rowman & Littlefield, 2014)
In Introduction to Reference and Information Services in Today's School Library, one of America's premier school library educators covers the A-Z of both reference and information services for today's library. Lesley Farmer discusses everything from teaching students how to use sources to both in-person and virtual reference service.